A Human rights approach to clinical nutrition : addressing the challenges of disease-related malnutrition in resource limited settings - Hardy, Gil; Sutanto, Luciana B (Indonesian Nutrition Association, 2025)
A human rights-based approach can be the cornerstone in the field of clinical nutrition. By endorsing the five principles of the Vienna Declaration, the global clinical nutrition network is developing initiatives and strategies for implementing programmes for improving awareness, advocacy, education, research and collaboration. The prevalence of disease-related malnutrition in hospitalized patients is higher in Asian resource limited countries than in Europe with unacceptably high nutrition risks in cancer, tuberculosis and intestinal failure in Indonesia. The international human rights working group has recommended practical steps involving evaluation of the applicability of the current international guidelines, and development of new resource-stratified guidelines followed by promotion and implementation.